PELATIHAN PRODUKSI VIDEO DOKUMENTER UNTUK SISWA DI SMK MAARIF 4 KEBUMEN JAWA TENGAH - Atmaja Septa Miyosa; Surasa .; Sudarman .; Priya Wintar Yuhanto (LPPM Institut Desain dan Bisnis Bali, 2022)
Documentary video production training was conducted by animation study program lecturers for students of SMK Maarif IV, Kebumen, Central Java from March 1, 2022 to March 5, 2022. The main problem is competence of students to make documentary videos and wise of Headmaster of the school to have a product, such as school profile videos and learning videos. The purpose of the activity is to make good and artistic video production works. The methods used are lectures, questions and answers, demonstrations, and presentations of works. The main material presented is Introduction to Production, Writing of Documentary Video Production Scripts, Introduction to Video Cameras, Audio, and Lighting, Non Linear Editing. The practice of taking pictures is carried out entirely within the school environment. The results of the activity are in the form of a documentary video entitled Maarif IV SMK school profile and a learning video entitled Power Amplifier Assembly. The presentation of the work shows that the video work produced is quite good and can be developed by students independently.